Lymph Node Dissection of Choice in Older Adult Patients with Gastric Cancer (2024)
Background: Although the current literature has shown an increasing interest in surgical treatment of gastric cancer (GC) in older adults in recent years, there is still no consensus on proper management in this subgroup of patients. This study was designed with the objective of evaluating the current evidence that compares limited lymph node dissection with extended lymph node dissection in older adult patients (?65 years) coursing with resectable GC. Methods: A systematic review of PubMed, Cochrane library, and ScienceDirect was performed according to PRISMA guidelines. All studies before 2018 were selected using a systematic review by Mogal et al. Studies were eligible for this meta-analysis if they were randomized controlled trials or non-randomized comparative studies comparing limited lymph node dissection versus extended lymph node dissection in patients with resectable GC taken to gastrectomy. Results: Seventeen studies and a total of 5056 patients were included. There were not any statistically significant differences in OS (HR = 1.04, CI95% = 0.72–1.51), RFS (HR = 0.92, CI95% = 0.62–1.38), or CSS (HR = 1.24, CI95% = 0.74–2.10) between older adult patients taken to limited and extended lymphadenectomy in addition to gastrectomy as the current surgical treatment for GC. Although a higher rate of major complications was observed in the extended lymphadenectomy group, this difference was not statistically significant in incidence between both groups of patients (OR = 1.92, CI95% = 0.75–4.91). Conclusions: Limited lymphadenectomy must be considered as the better recommendation for surgical treatment for GC in older adult patients, considering the oncological outcomes and lower rates of complications compared with more radical lymph node dissections.